Dynamics of Population and Secondary Productivity of Isognomon isognomum Clams (Bivalvia: Isognomonidae) in the Waters of Tapulaga Beach, Konawe - Aita Rahma Kartika Jumain; Bahtiar Bahtiar; Abdul Hamid (Masyarakat Moluska Indonesia, 2026)
ABSTRACT Isognomon isognomum is a bivalve species widely harvested as a local food resource, yet its natural populations show signs of decline. This study aimed to estimate the secondary productivity of I. isognomum in the coastal waters of Tapulaga, Southeast Sulawesi. Field sampling was conducted from September 2024 to February 2025, yielding a total of 360 individuals. Shell length and total weight were measured using a caliper and an analytical balance, respectively. Ash-free dry mass (AFDM) was obtained by combusting dried tissues in a muffle furnace at 600°C for four hours. Density, growth, production, and biomass were analyzed using the Mann–Whitney test, ELEFAN (FiSAT II), and standard ecological productivity formulas. Density analysis showed the highest abundance in December (14 ind/m²) and the lowest in January (9.78 ind/m²). The Mann–Whitney test (p < 0.05) indicated significant differences between December and January compared to other sampling months. Growth parameters revealed an asymptotic length (L∞) of 13.80 cm and a growth coefficient (K) of 0.71. The highest production occurred in the 6.9–7.8 cm size class, reaching 1,181.97 g AFDM/m²/year, while peak biomass (10,703.42 g AFDM/m²) was recorded in the 8.9–9.8 cm size class. The mean P/B ratio was 0.12/year, suggesting a low recovery potential for I. isognomum populations. Keywords: Isognomon isognomum, secondary productivity, Tapulaga coast ABSTRAK Isognomon isognomum merupakan bivalvia yang dimanfaatkan masyarakat sebagai sumber pangan dan cenderung populasinya menurun di alam. Studi ini bertujuan untuk mengetahui produktivitas sekunder kerang I. isognomum di perairan Pantai Tapulaga Sulawesi Tenggara. Penelitian ini dilakukan pada bulan September 2024-Februari 2025. Jumlah sampel yang dikumpulkan selama penelitian sebanyak 360 individu. Sampel kerang diukur panjang cangkangnya dan beratnya masing-masing menggunakan jangka sorong, dan timbangan analitik. Massa kering bebas abu (MKBA) didapatkan dengan membakar daging kering menggunakan tanur selama 4 jam pada suhu 600°C. Data kepadatan, pertumbuhan, produksi dan biomassa masing-masing dianalisis menggunakan uji Mann Whitney, ELEFAN (FiSAT II), dan formula yang telah baku. Hasil analisis kepadatan menunjukkan kepadatan kerang I. isognomum tertinggi pada bulan Desember dan terendah pada bulan Januari dengan nilai masing-masing sebesar 14 dan 9,78 ind/m2. Hasil uji Mann Whitney (p<0.05) menunjukkan ada perbedaan signifikan antara bulan Desember dan Januari dari bulan-bulan lainnya. Parameter pertumbuhan (panjang maksimum dan koefisien pertumbuhan) masing-masing sebesar L∞ = 13,80, dan K = 0,71. Produksi kerang tertinggi ditemukan pada ukuran 6,9-7,8 cm dengan nilai 1.181,97g mkba/m2/thn dan biomassa tertinggi ditemukan pada ukuran 8,9-9,8 cm sebesar 10.703,42 g mkba/m². Nilai rata-rata rasio P/B keseluruhan sebesar 0,12/tahun yang berarti bahwa kemampuan pulih kerang I. isognomum berada dalam kategori rendah. Kata Kunci: Isognomon isognomum, Produktivitas sekunder, Pantai Tapulaga